Are there bubbles in exchange rates? Some new evidence from G10 and emerging market economies - Hu, Y.; Oxley, Leslie (Elsevier BV * North-Holland, 2017)
The existence, or otherwise, of bubbles has become a topical issue in economics and finance, particularly following the Global Financial Crisis. Using the generalized sup ADF (GSADF), unit root tests of Phillips et al. (2015a, PSY) we investigate evidence for exchange rate bubbles in some G10, Asian and BRICS countries from Mar.1991-Dec.2014. We conclude that the US$-Mexican Peso crisis of 1994–95 was a bubble. Of particular interest to financial market trading, is that newly emerging countries, with relatively shallow financial markets, may be more likely to exhibit bubbly behavior in foreign exchange markets than more mature G10 countries.